PENGARUH POSISI MENYUSUI SECARA BIOLOGIC NURTURING BABY LED FEEDING TERHADAP PENURUNAN RASA NYERI POST SECTIOCAESAREA DI RUMAH SAKIT UMUM SEMBIRING DELITUA TAHUN 2020 - Joko Sutejo; Reisy Tane (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2022)
The Effect of Biologic Nurturing Baby Led Feeding Position on The Decrease in Post Sectio Caesarean Pain at Sembiring Delitua Hospital in 2020. Undergraduate Thesis. Nursing Study Program, Faculty of Nursing and Midwifery, Deli Husada Delitua Health Institute. Abdominal pain is a major problem in post-caesarean section mothers. Many post sectio mothers do not want to breastfeed their babies because of pain. As well breast milk is very good for newborns. This study aims to determine the effect of the position of biologic nurturing baby led feeding on the decrease in post sectio caesarean pain. This research uses quantitative design with a quasi experimental design with one group pretest posttest design without any comparison or control group. The data were analyzed using the Wilcoxon test. There were 38 available samples taken by purposive sampling method. The data were collected by using observation sheets of 38 respondents. The results with univariate analysis showed that 12 people (31.6%) had severe pain (31.6%) and moderate pain (68.4%). The results of the bivariate analysis obtained a p-value of 0.000 <0.05, which means that there is an effect of the position of biologic nurturing baby led feeding on the decrease in post-caesarean section maternal pain at Sembiring Delitua Hospital in 2020. We can conclude that it can be applied both in hospital services and in the community, or even as a learning entry in dealing with post sectio caesarean pain.